Inferior vena cava filters: a review - Barajas-Colón, José Ángel; Barrera-Mera, Baltazar; Banegas-Ruiz, Rodrigo; Vargas-Morales, José Juan; Barrera-Calva, Elvira; Castillo-Martínez, Daniel Benito; Grajeda-Chávez, Obed Horacio; Soulé-Martínez, Christian E.; Gómez-Mendoza, Francisco Fabián; Mendoza-Aceves, Rodrigo; Radilla-Flores, Mariana del Carmen; Espinosa-Queb, Nelson Niels; et al. (International Journal of Research in Medical Sciences, 2021)
Venous thromboembolism is an entity that ranges from deep vein thrombosis to pulmonary embolism, both are highly prevalent diseases in our environment and potentially fatal. The intention of this review is to compile information regarding the indications, contraindications, complications and comparison of different therapeutic methods in order to create an algorithm. An exhaustive review was performed with the available literature, using the PubMed, ScienceDirect, Scopus and Cochrane databases from 2004 to 2021. The search criteria were formulated to identify reports related to inferior vena cava filters. Venous thrombosis manifested as deep vein thrombosis or pulmonary embolism is a highly prevalent disease in our setting with high morbidity and mortality. Currently, different therapeutic options have been presented to address this pathology, in this review we focus on the developments regarding the use of vena cava filters. Reviewing the indications for the placement of a vena cava filter, we find absolute indications such as a contraindication to anticoagulation and high risk of massive pulmonary embolism. Pulmonary thromboembolism is a disease with high prevalence and mortality, we have highly effective and novel treatments such as the vena cava filter, patients should be selected carefully always taking into account the absolute and relative indications.